Comparative Religious Ethics Among the Ruins. Issue 3 (September 2014) - Lee, Jung
Abstract This is a response to the recent essay by Elizabeth M. Bucar and Aaron Stalnaker on "Comparative Religious Ethics as a Field of Study." I clarify my earlier positions on method and virtue in comparative religious ethics and try to respond to some of the issues that Bucar and Stalnaker raise in regard to my arguments specifically and the field more generally. I argue that while we need not measure the practical impact of scholarly work in comparative religious ethics purely in terms of political or social action, I nevertheless worry that defining the goals of comparative inquiry in terms of the production of bewilderment, intellectual vertigo, or skeptical questions can lead to impressionistic or therapeutic methodological norms. In a similar vein, I refine my earlier position on externalism that acknowledges the impossibility of a purely externalist approach but also notes the desirability of coming to understand others "in their own terms" prior to engaging in the process of transmutation. I also question Bucar and Stalnaker's pessimism about the potential of producing "rigorously convincing ethical theory from the lived experience of regular folk, " suggesting that perhaps we are working with different conceptions of the sociology of knowledge. Finally, I consider whether we are currently in the midst of an epistemological crisis and conclude with some reflections on the rationality of the craft of comparative religious ethics.